2018
DOI: 10.1007/s00737-018-0867-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in legal outcomes of filicide in Austria and Finland

Abstract: Female offenders of filicide have been found to receive more lenient legal handling than male offenders. We aimed to discover these possible gender differences in the legal outcome of filicide cases. This was a binational register-based study covering all filicide offenders in Austria and Finland 1995-2005. We examined the legal outcomes of the crimes of all living offenders (64 mothers and 26 fathers). Mothers received a conviction of murder and life imprisonment less often than fathers. Within psychotic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…However, several studies have reported aggressive behavior against intimate partners [60,61] and children [62] in individuals with a borderline personality disorder. Another study found that filicidal mothers, compared to fathers, were more subject to compulsory psychiatric hospitalization than to incarceration [63]. We published a report of two cases of filicide and attempted filicide, both with the diagnosis of schizophrenia [64].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported aggressive behavior against intimate partners [60,61] and children [62] in individuals with a borderline personality disorder. Another study found that filicidal mothers, compared to fathers, were more subject to compulsory psychiatric hospitalization than to incarceration [63]. We published a report of two cases of filicide and attempted filicide, both with the diagnosis of schizophrenia [64].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, filicidal women have a less extensive criminal history than men (Eriksson et al 2016;Lysell et al 2014;Putkonen et al 2011;Sidebotham and Retzer 2018;Wilczynski 1997). Finally, several studies have noted a markedly different perception and legal treatment of men and women who killed their children (Amon et al 2018;Flynn et al, 2013;Wilczynski, 1997). Women are treated more leniently; they are less likely than men to be prosecuted, less likely to be convicted of murder, receive shorter sentences, and are more likely to receive a psychiatric disposal rather than a custodial sentence.…”
Section: Comparing Filicidal Mothers To Filicidal Fathersmentioning
confidence: 99%
“…She was also involuntarily committed. A study [32] found that filicidal mothers, compared to patricidal daughters, received more sentences of involuntary hospitalization than incarceration, as illustrated by this case.…”
Section: Discussionmentioning
confidence: 75%